PERAN CAMAT DALAM PENYELESAIAN KONFLIK LAHAN ANTARA NAGARI TARAM DENGAN NAGARI PILUBANG KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA TAHUN 2022 - ', Rahmadita; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The importance of government participation in accelerating the resolution of social conflicts in village communities, especially in the land sector, is a crucial thing that must be paid attention to by the sub-district government. Such as the land conflict that occurred between Nagari Taram and Nagari Pi Lubang in 2017 which killed one of the residents during a clash in the land area on the border between the two nagari. Overall, this research aims to find out the role of the sub-district head in resolving land conflicts in Harau District. To achieve this goal, descriptive qualitative research was carried out to identify the internal and external environment of the object of this research. The results of this research show that the role of the Harau sub-district head has been good in carrying out his role, by coordinating with the community in carrying out FGD (Focus Group Discussions) activities to formulate this problem in a family manner, and by inviting both parties to the conflict and the Regency PPBN team, including the sub-district head, Assistant Regency Regional Secretary, DPMD (Village Community Empowerment Service), Wali Nagari, Ninik Mamak (KAN) of both villages, Head of Jorong, Bamus, researchers from UNP, and several Community Leaders to complete the administrative clarity of the boundaries between Nagari Taram and Nagari Pi Lubang. This then aims to prevent land conflicts from occurring again. Keywords: Role, Subdistrict Head, Land Conflict, FGD (Focus Group Discussions)